ENHANCING STUDENTS’ CONCEPTUAL UNDERSTANDING IN MATHEMATICS THROUGH COMIC-BASED LEARNING: A MIXED-METHODS STUDY - Mutaqin, Izay Zaenal; Alas’ari, Dicky Zaini Abdullah; Abdul Muin, Azwan Rhamdhan; Fauzi, Rival Muhamad (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2026)
Conceptual understanding lies at the heart of meaningful mathematics learning, yet instructional practices in many contexts remain procedural and memorization-based, limiting students’ ability to connect symbolic, verbal, and visual representations. Addressing this gap, this study investigates the effectiveness and cognitive–affective mechanisms of comic-based learning in improving students’ conceptual understanding of mathematics and develops a new theoretical model, the Visual–Narrative Learning Framework (VNLF). Employing a mixed-methods sequential explanatory design, the research involved 60 eighth-grade students divided into an experimental group (comic-based instruction) and a control group (conventional teaching). Data were collected through conceptual understanding tests, motivation questionnaires, interviews, and classroom observations. Quantitative data were analyzed using t-tests, gain scores, and effect size, while qualitative data underwent thematic analysis. Findings revealed that the experimental group achieved significantly higher conceptual understanding (M = 93.6 vs. 81.4; t(58) = 7.25, p .001; d = 1.56, large effect; g = 0.72, high category). Comics facilitated the transformation of symbolic ideas into visual–narrative representations, increasing emotional engagement and intrinsic motivation. The integrated results produced the VNLF, which explains conceptual learning as the simultaneous interaction of visualization, narration, and teacher mediation. Theoretically, this study extends the Cognitive Theory of Multimedia Learning by incorporating affective and social dimensions into visual–narrative mathematics instruction. Practically, it positions comic-based learning as an integrative pedagogical strategy that enhances students’ numeracy, visual literacy, and engagement, supporting the goals of the Merdeka Curriculum and advancing digital transformation in mathematics education.